PENDAMPINGAN MODEL DESA WISATA BERBASIS TERNAK DI DESA BATU KUTA LOMBOK BARAT - Alimuddin, Alimuddin; Syukur, Abdul; Hilyana, Siti; Harmayani, Ria; Fitriyah, Abyadul; Mariani, Yuni; Andry Kartika, Ni Made; Andriana Fajri, Nefi; Permadi, Hari; Gunadi, Sahrul; Damar Pamenang, Galang; Aminah Zaim Alyaminy, Ishmah Humaidatul; Jupri Hadi, Marham; Nazar Fajri, Lalu Moh. (JURNAL PENGABDIAN MANDIRI, 2024)
Livestock-based tourism villages are one option in developing village potential. Apart from being a significant source of income for local communities, it is also able to develop the agricultural and livestock sectors, able to improve the local economy and create jobs for its residents. Tourists who visit villages not only have a direct economic impact obtained from visiting fees and purchasing local products, but can also strengthen small and medium businesses operating around the village. Batu Kuta Village, West Lombok has a village land area of ​​around 40,000 m2 which is called Kebon doe, which is currently a garden area planted with coconut and fruit plants which are no longer productive and have potential, so community service (PKM) is very necessary, related to the preparation of appropriate structuring and management strategies through the preparation of concepts and models for livestock-based tourism villages. The PKM method is implemented using the methods of observation, planning, implementation, follow-up, evaluation and mentoring. Mapping of village potential, preparation of concepts and models for the livestock-based Batu Kuta tourism village were carried out in coordination with the village government and local community. The concept and model of a livestock-based tourism village has the potential to be adopted and realized in Batu Kuta Village. Achievement of the objectives of this PKM activity reached 100% and 98% of participants were satisfied with the overall activity. Evaluation is carried out during the process and at the end of the activity, as well as giving questionnaires to participants. The role of all parties, especially youth organizations, Pokdarwis members, village government and the community as well as assistance from practitioners and academics, is expected to continue to actively participate and be communicative and cooperate with each other in facing concerns and challenges regarding the sustainability of the development of livestock-based tourism villages.